Anti-icing photo-thermal super-hydrophobic composite membrane as well as preparation method and application thereof
By constructing a photothermal super-hydrophobic composite film on a PVDF nanofiber base film, the problems of poor durability and environmental adaptability of existing anti-icing materials are solved, and an efficient and stable anti-icing effect is achieved.
Patent Information
- Application Number
- CN202411453618.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing anti-icing materials have poor durability, unstable, high cost and insufficient environmental adaptability, especially on flexible substrates.
A PVDF nanofiber base film is used as a flexible substrate, combined with a photothermal layer and a hydrophobic layer, and the PVDF nanofiber base film is prepared by electrospinning, and the PPy-PVA functional layer and PDMS@SiO2 hydrophobic layer are coated on its surface to form a light Thermal superhydrophobic composite membrane.
It achieves ultra-high hydrophobicity, good self-cleaning performance and excellent stability, significantly prolongs the time for water droplets to freeze into ice, and has excellent active anti-icing performance and passive anti-icing effect.
Smart Images

Figure CN119332516A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-icing materials, and in particular to an anti-icing photothermal super-hydrophobic material and a preparation method and application thereof. Background Art
[0002] Icing is a common phenomenon in nature. The formation and accumulation of ice will cause great damage to transportation, wind power generation, housing and power transmission systems, thus causing many inconveniences to people's production and life and even significant economic losses. Developing a long-term anti-icing and de-icing technology is crucial to the safety and efficiency of aviation, electricity, communications, energy and other fields. Traditional de-icing methods, such as mechanical de-icing, thermal de-icing and chemical de-icing, are usually inefficient, costly and harmful to the environment. Therefore, it is crucial to develop a more efficient and environmentally friendly anti-icing and de-icing strategy.
[0003] Superhydrophobic materials form micro-nano structures and low surface energy coatings on the surface, allowing water droplets to quickly bounce or roll off on inclined surfaces, thereby effectively preventing ice from forming. The photothermal superhydrophobic coating technology, which combines superhydrophobic micro-nano structures with photothermal materials, can increase the surface temperature by absorbing solar radiation. In addition, the superhydrophobic surface can quickly remove melted water and maintain high solar thermal performance. It can work even in the absence of sunlight, improving the stability and efficiency of material applications. At present, researchers have achieved certain research results in this field. For example, combining laser etching with spin coating or deposition technology. Such a process is not only time-consuming and labor-intensive, but also increases production difficulty and cost (Reference 1: Z. Lin, C. Ma, Z. Ma, L. Gao, W. Chen, G. Chen, Laser etching ultra-black coating with novel anti-icing performance, Chemical Engineering Journal, 466 (2023) 143067. https: / / doi.org / https: / / doi.org / 10.1016 / j.cej.2023.143067). In addition, the extensive use of expensive chemical reagents such as perfluorinated compounds has also increased the economic burden, and most of the preparation processes will also cause environmental pollution (Reference 2: GY Liu, Y. Yuan, RJ Liao, HY Xiang, L. Wang, Q. Yu, C. Zhang, Robust self-healing superhydrophobic aluminum surface with excellent anti-icing performance, Surfaces and Interfaces, 28 (2022) 101588. https: / / doi.org / https: / / doi.org / 10.1016 / j.surfin.2021.101588). At the same time, considering the temperature rise effect brought about by the photothermal conversion process, directly applying the photothermal superhydrophobic coating to the equipment may cause the equipment to overheat. In addition, the anti-icing coating requires long-term maintenance, and there are problems of poor long-term anti-icing effect and poor durability.
[0004] Current research focuses on high-performance anti-icing / de-icing coatings on rigid, flat substrates, such as metal plates, glass, and wood. However, there is relatively little research on flexible substrates such as textiles, sponges, and foams. The preparation of a photothermal superhydrophobic anti-icing material that is suitable for both flexible and rigid substrates will greatly expand its application range. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a flexible photothermal super-hydrophobic composite film and a preparation method thereof, so as to solve the problems of poor durability, instability, high cost and environmental adaptability of anti-icing materials in the prior art.
[0006] A first aspect of the present invention provides a photothermal super-hydrophobic composite membrane, which comprises a PVDF nanofiber base membrane, a photothermal layer attached to the PVDF nanofiber base membrane, and a hydrophobic layer attached to the photothermal layer.
[0007] Preferably, the photothermal layer comprises light-absorbing nanoparticles, a stabilizer and an oxidant; the light-absorbing nanoparticles are polypyrrole nanoparticles, the stabilizer is polyvinyl alcohol, and the oxidant is one or more selected from FeCl3, FeCl3.6H2O.
[0008] In some specific embodiments, the oxidant is FeCl3.6H2O.
[0009] Preferably, the hydrophobic layer comprises functional particles, a hydrophobic modifier and a curing agent; the functional particles are one or two selected from titanium dioxide and silicon dioxide, the hydrophobic modifier is a polydimethylsiloxane prepolymer, and the curing agent is a polydimethylsiloxane curing agent.
[0010] In some specific embodiments, the functional particles are silicon dioxide.
[0011] Preferably, the mass ratio of the light absorbing nanoparticles, the stabilizer and the oxidant in the photothermal layer is 0.1-2:0.1-0.5:1-10.
[0012] More preferably, the mass ratio of the light absorbing nanoparticles, the stabilizer and the oxidant in the photothermal layer is 0.1-1:0.1-0.5:5-10.
[0013] Preferably, the mass ratio of the functional particles, the hydrophobic modifier and the curing agent in the hydrophobic layer is 0.1-10:0.1-10:0.01-1.
[0014] More preferably, the mass ratio of the functional particles, the hydrophobic modifier and the curing agent in the hydrophobic layer is 0.1-1:0.1-1:0.01-0.1.
[0015] Preferably, the photothermal super-hydrophobic composite membrane further comprises a cross-linking agent for fixing the photothermal layer to the PVDF nanofiber base membrane.
[0016] Preferably, the cross-linking agent is glutaraldehyde.
[0017] Preferably, the photothermal super-hydrophobic composite film has a thickness of 60 to 100 μm.
[0018] More preferably, the thickness of the photothermal super-hydrophobic composite film is 80-100 μm.
[0019] Preferably, the surface water contact angle of the photothermal super-hydrophobic composite film is greater than 150°
[0020] The second aspect of the present invention provides a method for preparing the above-mentioned photothermal super-hydrophobic composite membrane, which includes coating a dispersion of a photothermal layer on the surface of a PVDF nanofiber base membrane to form a photothermal layer and coating a dispersion of a hydrophobic layer on the surface of the photothermal layer to prepare the photothermal super-hydrophobic composite membrane.
[0021] Preferably, the PVDF nanofiber-based membrane is prepared by electrospinning.
[0022] Preferably, the electrospinning solution uses DMF and / or acetone as solvent, and the concentration of PVDF in the spinning solution is 10-20 wt %.
[0023] Preferably, the electrospinning parameters are any one or more of the following: pushing speed of 1-10 μL / min, voltage of 25-40 kV, collection distance of 10-20 cm, spinning temperature of 20° C.-30° C., and spinning humidity of 20%-40%.
[0024] Preferably, the dispersion of the photothermal layer is sprayed onto the surface of the PVDF nanofiber base film to form the photothermal layer, and the coating amount of the dispersion of the photothermal layer is 0.1-10 ml / cm 2 .
[0025] More preferably, the coating amount of the photothermal layer dispersion is 0.1 to 1 ml / cm 2 .
[0026] Preferably, the method further comprises immersing the PVDF nanofiber base membrane coated with the photothermal layer in a crosslinking solution to crosslink and fix the photothermal layer, wherein the crosslinking solution comprises a crosslinking agent and a solvent, wherein the crosslinking agent is glutaraldehyde, and the solvent is one or more of acetone, water, ethanol, and ether.
[0027] Preferably, the dispersion of the photothermal layer is formed by dispersing the materials in the photothermal layer with a solvent, and the solvent is selected from deionized water. Based on the addition amount of 1g of stabilizer, the addition amount of the solvent is 5 to 20mL.
[0028] More preferably, based on the addition amount of 1 g of the stabilizer, the addition amount of the solvent is 10 to 20 mL.
[0029] Preferably, the dispersion of the hydrophobic layer is formed by dispersing the material in the hydrophobic layer with a solvent, and the solvent is one or more selected from ethyl acetate, ethanol, and deionized water. Based on the addition amount of 1g of functional particles, the addition amount of the solvent is 100-500mL.
[0030] More preferably, based on the addition amount of 1 g of functional particles, the addition amount of the solvent is 100 to 300 mL.
[0031] In some specific embodiments, the solvent in the cross-linking solution is acetone and water.
[0032] Preferably, the volume ratio of acetone to water is 1 to 5:1, more preferably 1 to 3:1.
[0033] In some specific embodiments, the volume ratio of acetone to water is 3:2.
[0034] Preferably, the pH of the cross-linking solution is 1-3.
[0035] In some specific embodiments, the pH of the cross-linking solution is 2.
[0036] Preferably, the concentration of the crosslinking agent in the crosslinking solution is 0.5 wt %.
[0037] Preferably, the cross-linking time is 2 hours.
[0038] Preferably, the method further comprises spraying a dispersion of the hydrophobic layer onto the surface of the cross-linked photothermal layer, wherein the coating amount of the dispersion of the hydrophobic layer is 0.1 to 10 ml / cm 2 .
[0039] More preferably, the coating amount of the hydrophobic layer dispersion is 0.1 to 1 ml / cm 2 .
[0040] Preferably, the method further comprises a solvent welding step, wherein the solvent welding is to place the coated photothermal super-hydrophobic composite film at 60 to 100° C. for 3 to 10 hours.
[0041] More preferably, the temperature of the solvent welding is 70-90° C., and the time of the solvent welding is 4-8 hours.
[0042] The third aspect of the present invention provides an application of the above-mentioned photothermal super-hydrophobic composite film as an anti-icing film
[0043] As described above, the photothermal super-hydrophobic composite film of the present invention has the following beneficial effects:
[0044] 1. The photothermal super-hydrophobic composite film prepared in this application has super-high hydrophobicity. With the help of this super-hydrophobic function, an excellent passive anti-icing effect can be achieved, which can significantly prolong the time for water droplets to freeze into ice.
[0045] 2. The photothermal super-hydrophobic composite film prepared in this application has excellent active anti-icing performance. Compared with the PVDF film without a photothermal layer, the freezing time of water droplets can be extended by more than 2 times, and it has excellent photothermal conversion performance.
[0046] 3. The photothermal super-hydrophobic composite film prepared in the present application has good self-cleaning properties. When it is immersed in aqueous solutions of different colors, there is no water stain or color deposition on the surface of the film after it is taken out.
[0047] 4. The photothermal super-hydrophobic composite film prepared in this application has excellent stability and will not corrode or deform under various acid, alkali, salt, cold or hot conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 Shown is a schematic diagram of the preparation process of the photothermal super-hydrophobic composite film of the present invention.
[0049] Figure 2 A shows the surface morphology of the PPy-PVA / PVDF fiber membrane prepared in Example 3 of the present invention using a 0.25 mL PPy-PVA slurry spraying amount.
[0050] Figure 2 B shows the surface morphology of the PPy-PVA / PVDF fiber membrane prepared in Example 3 of the present invention using a 0.5 mL PPy-PVA slurry spraying amount.
[0051] Figure 2 C shows the surface morphology of the PPy-PVA / PVDF fiber membrane prepared in Example 3 of the present invention using a 0.75 mL PPy-PVA slurry spraying amount.
[0052] Figure 2 D shows the surface morphology of the PPy-PVA / PVDF fiber membrane prepared in Example 3 of the present invention using a 1 mL PPy-PVA slurry spraying amount.
[0053] Figure 3 It shows the temperature rise trend of the photothermal conversion of the PPy-PVA / PVDF fiber membrane under 1 sun conditions in Example 3 of the present invention.
[0054] Figure 4 A shows the surface morphology of the PPy-PVA-GA / PVDF composite membrane prepared in Example 4 of the present invention in which the volume ratio of acetone to water in the cross-linking solution is 60:40.
[0055] Figure 4 B shows the surface morphology of the PPy-PVA-GA / PVDF composite membrane prepared in Example 4 of the present invention in which the volume ratio of acetone to water in the cross-linking solution was 70:30.
[0056] Figure 4 C shows the surface morphology of the PPy-PVA-GA / PVDF composite membrane prepared in Example 4 of the present invention in which the volume ratio of acetone to water in the cross-linking solution is 80:20.
[0057] Figure 5 Shown are the water contact angle test results of different PPy-PVA-GA / PVDF composite films prepared using cross-linking solutions with different volume ratios of acetone and water in Example 4 of the present invention.
[0058] Figure 6 A shows the surface morphology of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film prepared in Example 5 of the present invention using a spray amount of 1 mL of hydrophobic dispersion.
[0059] Figure 6 B shows the surface morphology of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film prepared in Example 5 of the present invention using a spray amount of 1.5 mL of hydrophobic dispersion.
[0060] Figure 6 C shows the surface morphology of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film prepared in Example 5 of the present invention using a 2 mL spray amount of the hydrophobic dispersion.
[0061] Figure 7 It shows the test curve chart of the photothermal conversion performance of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film and the PPy-PVA / PVDF photothermal composite film in Example 5 of the present invention.
[0062] Figure 8 It shows the temperature change trend of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite film under different irradiation conditions in Example 5 of the present invention.
[0063] Fig. 9 A shows the freezing process of the droplets on the PPy-PVA / PVDF photothermal composite film in Example 6 of the present invention.
[0064] Fig. 9 B shows the freezing process of the droplet on the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite film in Example 6 of the present invention.
[0065] Fig.10 It shows a comparison chart of the freezing time of droplets on the PPy-PVA / PVDF photothermal composite membrane and the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite membrane in Example 6 of the present invention.
[0066] Fig.11 A shows the freezing process of the droplets on the PVDF nanofiber base membrane in Example 6 of the present invention.
[0067] Fig.11 B shows the freezing process of the droplet on the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite film in Example 6 of the present invention.
[0068] Fig.12 It shows a comparison of the freezing time of droplets on the PVDF nanofiber-based membrane and the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite membrane in Example 6 of the present invention.
[0069] Fig.13 It shows a comparison diagram of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film after being placed in and taken out of different solutions in Example 6 of the present invention. DETAILED DESCRIPTION
[0070] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0071] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0072] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0073] In view of the poor durability, instability, high cost and environmental adaptability of anti-icing materials in the prior art, this application selects a hydrophobic PVDF nanofiber membrane with better strength and lower thermal conductivity as a flexible substrate, wherein the hydrophobic support layer can prevent the surface hydrophilic photothermal slurry from penetrating into the fiber membrane and play a role in thermal isolation. In view of the film integrity and complexity of the preparation process of the photothermal functional layer, PVA (polyvinyl alcohol) is used as a stabilizer in this patent, and PPy (polypyrrole) particles are dispersed and polymerized by a simple one-step method. After FeCl3 is added as an oxidant of the PVA / Fe cation complex, PPy nanoparticles are manufactured using the reaction sites of the pyrrole monomer and the complex, and the reaction forms a PPy-PVA slurry. Then, the PPy-PVA functional layer is coated on the surface of the PVDF nanofiber membrane and cross-linked to achieve resistance to hydrolysis. In order to achieve the super-hydrophobicity required for passive anti-icing, this patent chooses to construct a multi-scale micro-nano super-hydrophobic structure by combining low-surface energy material PDMS and nanoparticle SiO2. PDMS can reduce the surface energy of the composite membrane, further enhance the repellency, and effectively improve the performance of the membrane.
[0074] The anti-icing photothermal super-hydrophobic composite film prepared in the present application has ultra-high hydrophobicity, good self-cleaning performance and excellent stability, and can play an anti-icing role through the active anti-icing of the photothermal layer and the passive anti-icing of the super-hydrophobic layer. The photothermal super-hydrophobic composite film of the present application can be coated or pasted on the surface of the hard substrate or flexible substrate to be protected to play a role in protecting the substrate from icing.
[0075] Example 1
[0076] This embodiment is a process for preparing an anti-icing photothermal super-hydrophobic composite film.
[0077] Step 1: Preparation of PVDF nanofiber-based membrane.
[0078] Prepare 15wt% PVDF / DMF spinning solution: Weigh a certain amount of PVDF powder (Mw=573000g / mol, Solvay Shanghai Co., Ltd.) and dissolve it in DMF. Stir continuously in a 70℃ oil bath for 3 days until the solution becomes transparent. Let it stand for 24 hours until all bubbles are removed. Take 5mL of spinning solution and inject it into a syringe with a stainless steel metal needle. Clamp the syringe on a micro-propellant pump and adjust the propulsion speed to 5uL / min. Apply a voltage of 28kV to energize the polymer solution, and then the droplets generate Taylor cones under the action of electrostatic repulsion, overcome surface tension to form a jet, and the generated nanofibers are collected on a metal roller wrapped in aluminum foil. The rotation speed of the roller is 500rpm / min, and the distance from the roller to the spinneret is 15cm. During the electrospinning process, the ambient temperature and humidity were 27 ± 5 °C and 30 ± 5%, respectively. Finally, the prepared PVDF nanofiber-based membrane was vacuum dried at 60 °C for 12 h to remove the residual solvent and hot-pressed at 155 °C for 10 min to improve the dimensional integrity of the membrane.
[0079] Step 2: Preparation of the photothermal functional layer of the composite film.
[0080] 1.5g PVA (86-89% hydrolysis degree, low molecular weight, catalog number: 041238, Thermo Fisher Scientific (China) Co., Ltd.) was dissolved in 20ml deionized water at 60°C for 20min, then cooled to room temperature and FeCl3.6H2O (0.23M) was added thereto. After the system changed from clear to yellow and balanced for 1h, 0.1M pyrrole monomer (analytical grade 9%, Shanghai Wendong Chemical Reagent Co., Ltd.) was added to the system, and the system temperature was kept at 5°C and stirred for 4h to form PPy-PVA slurry. After that, a certain amount of PPy-PVA slurry (0.25mL, 0.5mL, 0.75mL, 1mL, 1.25mL, 1.5mL) was loaded on the 3×3cm PVDF nanofiber membrane prepared in the above step 1 by spraying to obtain PPy-PVA / PVDF fiber membrane. Then, acetone and water were prepared into a solution in a certain ratio (60:40, 70:30, 80:20), and then 1.5M HCl solution was added to adjust its pH value to about 2, and an appropriate amount of 25% glutaraldehyde aqueous solution (GA) was added to the solution to prepare a cross-linking solution with a cross-linking agent concentration of 0.5wt%. The PPy-PVA / PVDF fiber membrane was soaked in 100mL of the cross-linking solution for 2h, and the PPy-PVA-GA / PVDF composite membrane was formed by cross-linking with GA.
[0081] Step 3: Preparation of super-hydrophobic layer of composite membrane.
[0082] 0.2g of fumed silica (7-40nm, Shanghai Titan) was added to 0.2g of polydimethylsiloxane prepolymer (PDMS prepolymer, 1wt%) and ultrasonically treated in 20mL of ethyl acetate for 1h. Subsequently, 0.02g of curing agent (PDMS prepolymer: curing agent) was added at a mass ratio of 10:1 and stirred for 10min to form a hydrophobic dispersion. Different volumes of hydrophobic dispersion (1mL, 1.5mL, 2mL) were sprayed onto the PPy-PVA-GA / PVDF composite membrane prepared in step 2 above to form a super-hydrophobic layer, and dried at 80°C for 5h to obtain a photothermal super-hydrophobic composite membrane PDMS@SiO2 / PPy-PVA-GA / PVDF.
[0083] The preparation process of the photothermal super-hydrophobic composite film of the present invention is as follows Figure 1 shown.
[0084] Example 2
[0085] The film thickness of the photothermal super-hydrophobic composite film prepared in Example 1 of the present invention was tested.
[0086] Specifically in accordance with ASTM E252-2006, the thickness of the PVDF fiber composite membrane was measured using a thousandths thickness gauge, and the average value was taken after three measurements at different locations of the PVDF fiber composite membrane. The test showed that the thickness of the PVDF fiber composite membrane was between 80-100 μm.
[0087] Example 3
[0088] In this example, PPy-PVA / PVDF fiber membranes were prepared by spraying different amounts of PPy-PVA slurry on PVDF nanofiber base membranes, thereby evaluating the structural characteristics and photothermal conversion performance of the photothermal composite membranes obtained with different amounts of PPy-PVA slurry.
[0089] 0.25mL, 0.5mL, 0.75mL, 1mL, 1.25mL and 1.5mL of PPy-PVA slurry were sprayed on 3×3cm PVDF nanofiber membranes by spraying in small amounts and multiple times through a 0.5mm spray gun to obtain PPy-PVA / PVDF fiber membranes, which were then placed in an oven at 50°C and dried for 10min to obtain photothermal composite membranes with different loading amounts.
[0090] Figure 2A-2D are the surface morphology images of the photothermal films under the scanning electron microscope at the above four different PPy-PVA slurry loadings (0.25mL, 0.5mL, 0.75mL, 1mL). The results show that at a loading of 0.25mL, the exposed fiber morphology can be clearly seen. As the loading increases to 0.75mL, only slight cracks exist in the surface photothermal layer. When 1ml of PPy-PVA slurry is used as a spraying liquid, the PPy-PVA slurry can completely cover the surface of the fiber membrane to form a complete photothermal layer. At the same time, the scanning electron microscope image at a large magnification shows that the small spherical PPy nanoparticles formed by polymerization are densely gathered on the surface.
[0091] In order to further verify the effect of the deposition amount of the PPy-PVA layer on the photothermal conversion of the PPy-PVA / PVDF fiber membrane, the photothermal conversion heating trend of the fiber membranes with different loading amounts under the irradiation condition of 1 sun of a xenon lamp solar simulator was tested. The specific test results are as follows: Figure 3 As shown in the figure (the horizontal axis represents the spraying amount, and the vertical axis represents the temperature). The results show that as the PPy-PVA slurry spraying amount gradually increases from 0.5 mL, the photothermal conversion temperature rise trend of the film gradually increases; while starting from 1 mL, as the PPy-PVA slurry spraying amount increases, the temperature rise trend line is not obvious.
[0092] Combination Figure 2 A-2D and Figure 3 It can be seen from the results that a complete photothermal layer can be formed on the membrane surface when the PPy-PVA slurry spraying amount is 1 mL. At the same time, further observation shows that with the increase of PPy-PVA slurry loading, the surface equilibrium temperature increases rapidly with the increase of spraying amount. However, after spraying 1 mL of PPy-PVA slurry, the photothermal layer equilibrium temperature rises limitedly when the spraying amount of PPy-PVA slurry continues to increase. Therefore, a spraying amount of 1 mL of PPy-PVA slurry can make the composite membrane surface have excellent photothermal conversion effect. Under 1 sun conditions, the temperature rise of the photothermal composite membrane can reach 77 °C.
[0093] Example 4
[0094] In this example, when the spraying amount of PPy-PVA slurry was 1 mL, only the volume ratio of acetone and water in the cross-linking solution was changed, so as to evaluate the structural characteristics of the cross-linked PPy-PVA-GA / PVDF composite membrane obtained under different volume ratios of acetone and water.
[0095] The PPy-PVA / PVDF fiber membrane was placed in a cross-linking solution with a volume ratio of acetone to water of 60:40, 70:30, and 80:20 and then taken out and washed with pure water, and cross-linked and dried at room temperature to obtain a PPy-PVA-GA / PVDF composite membrane with hydrolysis resistance at different cross-linking agent ratios.
[0096] Figure 4 A-4C is a surface morphology image of the PPy-PVA-GA / PVDF composite membrane observed by scanning electron microscopy after cross-linking using the above three cross-linking solutions of acetone and water in different ratios. The results show that the surface cross-linking layer still retains the rough structure of microscopic spherical particles, and the basically non-porous PPy-PVA hydrogel layer completely covers the nanofiber support layer. It can be seen that when the ratio of acetone to water is 60:40, the rough structure of the surface is more obvious, and as the acetone content in the cross-linking solution increases, the surface morphology tends to be smoother.
[0097] Furthermore, the water contact angle test was performed on the PPy-PVA-GA / PVDF composite membrane after crosslinking using the above three different ratios of acetone and water crosslinking solutions. Specifically, according to GB / T30447-2013, the water contact angle test was performed using an OCA40 dynamic contact angle meter (purchased from Dataphysics, Germany) to characterize the hydrophobicity of the membrane surface. Five different areas of each sample were measured and the average value was taken. The specific test results are shown in Figure 1. Figure 5 As shown in the figure (the horizontal axis represents the ratio of water to acetone, and the vertical axis represents the size of the water contact angle). The results show that when the ratio of acetone to water is 60:40, the water contact angle of the cross-linked composite film can reach 90°. As the amount of acetone further increases, the water contact angle shows a downward trend.
[0098] Combination Figure 4 A-4C and Figure 5 It can be seen from the results that when the ratio of acetone to water in the cross-linking solution is 60:40, the surface roughness of the cross-linked PPy-PVA-GA / PVDF composite membrane is obvious and the water contact angle is large; selecting a cross-linking ratio (60:40) that can provide a higher roughness surface is beneficial to further constructing a superhydrophobic layer on its surface, which increases the interaction area when the two interfaces are in contact and further improves its interlocking performance.
[0099] Example 5
[0100] In this example, when the spraying amount of PPy-PVA slurry was 1 mL and the ratio of acetone to water in the cross-linking solution was 60:40, only the spraying amount of the hydrophobic dispersion was changed, so as to evaluate the structural characteristics and photothermal conversion performance of the PDMS@SiO2 / PPy-PVA-GA / PVDF composite film obtained under different spraying amounts of the hydrophobic dispersion.
[0101] The PPy-PVA-GA / PVDF composite membrane and the hydrophobic dispersion were prepared according to the steps in Example 1. The hydrophobic dispersion was sprayed onto the surface of the PPy-PVA-GA / PVDF composite membrane in different volumes (1 mL, 1.5 mL, 2 mL) and dried at 80°C for 5 h to obtain the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super hydrophobic composite membrane.
[0102] The morphology of the three fiber composite membranes prepared with different volumes of hydrophobic dispersions was observed using a scanning electron microscope. Figure 6 As shown in A-6C, the results show that as the amount of hydrophobic dispersion sprayed increases, the number of particles on the film surface gradually increases, and finally spreads completely on the photothermal film surface at 2mL spraying amount. At the same time, it can be observed that the layered structure of the film surface is formed by stacking nanoparticles, thereby constructing micron-scale protrusions. The water contact angle of the prepared photothermal super-hydrophobic composite film is tested according to the method in Example 4. When the amount of hydrophobic dispersion sprayed is 2mL, the water contact angle of the film can reach 156°.
[0103] Further, the photothermal conversion performance of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film was tested under 1 sun conditions using the method in Example 3. The specific test results are as follows: Figure 7 As shown (the red dot trend line in the figure represents the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite film, and the blue triangle trend line represents the PPy-PVA / PVDF photothermal composite film). Figure 7 The results show that the temperatures of PPy-PVA / PVDF photothermal composite membrane and PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite membrane can reach 90.6℃ and 89.5℃, respectively, which indicates that the black PPy-PVA-GA cross-linked photothermal layer plays an important role, and the PDMS@SiO2 superhydrophobic layer has little effect on the photothermal properties of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite membrane.
[0104] Furthermore, repeated heating-cooling tests were performed under 1 sun, 1.4 sun, and 1.6 sun conditions to observe the temperature change of the film. Specifically, the film was irradiated with the light for 2 minutes and then turned off for 2 minutes to allow the film to cool naturally. Each condition was cycled 3 times. The specific results are shown in the figure. Figure 8 Under different irradiation conditions, the temperature changes on the surface of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film are similar, indicating that the photothermal super-hydrophobic composite film of the present application has stable photothermal conversion capability.
[0105] Example 6
[0106] In this example, the optimal PPy-PVA slurry spraying amount (1 mL), the ratio of acetone and water in the cross-linking solution (60:40) and the hydrophobic dispersion spraying amount (2 ml) in the above examples 3-5 were selected, and the same steps as in example 1 were adopted to prepare the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film, and its anti-icing performance, stability and self-cleaning performance were investigated.
[0107] In this example, 60uL of methylene blue solution was used as the frozen droplets, the cold source was controlled by a semiconductor cooling stage, and a xenon lamp was used as the test light source to measure the freezing time of the water droplets on the membrane surface to evaluate its anti-icing performance.
[0108] First, the freezing time of the droplets in dark and cold conditions was tested. Specifically, the sample was placed on a semiconductor cooling table, the temperature was set to -10°C, the relative humidity was 55±5%, and the cooling table was placed in a dark place to simulate a dark and cold environment. Then, a droplet (60uL) was dropped onto the sample surface with a pipette, and the freezing process of the droplet was recorded. The time required for the droplet to change from a liquid phase to a completely solid phase was defined as the freezing time.
[0109] Fig. 9 A-9B is the freezing process of a droplet in a cold environment in the dark. Fig.10 is the freezing time after the droplet lands on the PPy-PVA / PVDF photothermal composite membrane and the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite membrane. When the droplet contacts the PPy-PVA / PVDF photothermal composite membrane ( Fig. 9 A), the freezing time for the droplet to freeze into a hemispherical shape is 762s. However, when the droplet contacts the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite film, the freezing time is greatly delayed to 1113s. More importantly, the ice droplet maintains a spherical shape after freezing.
[0110] When droplets are added to the above two membranes, there are two reasons why the freezing processes of the two are different: the first reason is that the water contact angle of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite membrane is larger. When the water contact angle increases, the contact area between the water droplet and the substrate surface will decrease; the other reason is that different surfaces lead to different nucleation processes of water ice crystals. On the surface of the PPy-PVA / PVDF photothermal composite membrane, the ice nucleation process starts heterogeneously at the liquid-solid interface. However, on the surface of the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite membrane, since the hydrophobic layer on its surface has many micron-sized protrusions, the ice nucleation process on the membrane takes place at the three-phase interface (gas-liquid-solid), which prolongs the time for the droplet to completely freeze.
[0111] Furthermore, the freezing time of the droplets under cold light conditions was tested. Specifically, the sample was placed on a semiconductor cooling table, the temperature was set to -10°C, the relative humidity was 55±5%, and the cooling table was placed under a light source of 1sun to simulate a cold light environment. Then, a droplet (60uL) was dropped onto the sample surface with a pipette, and the freezing process of the droplet was recorded. The time required for the droplet to change from a liquid phase to a completely solid phase was defined as the freezing time.
[0112] Fig.11 A-11B is the freezing process of a droplet in a cold environment with light. Fig.12 is the freezing time after the droplet lands on the PVDF nanofiber base membrane and the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal superhydrophobic composite membrane. When the droplet contacts the PVDF nanofiber base membrane ( Fig.11 A), the freezing time for the droplet to freeze into a hemispherical shape is 714s. However, when the droplet contacts the PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film, the freezing time is greatly delayed to 1533s, and the ice drop remains spherical after freezing. This is because the PVDF nanofiber-based membrane without a photothermal layer cannot perform photothermal conversion, and the water droplets cannot absorb heat from the surface and can only rely on the heat from the environment, so they will be frozen quickly. The PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite membrane of the present application can not only absorb heat from the environment, but also absorb the heat brought by the photothermal conversion from the bottom photothermal layer, so its freezing time is significantly extended.
[0113] In addition, the stability and self-cleaning performance of the photothermal super-hydrophobic composite film were further investigated. The prepared PDMS@SiO2 / PPy-PVA-GA / PVDF photothermal super-hydrophobic composite film was placed in cold water (0°C), hot water (85°C), HCl solution (pH=2), 3.5wt% NaCl solution and NaOH solution (pH=12) for 6 minutes to test the self-cleaning property of the photothermal super-hydrophobic coating. All the above test solutions were dyed in different colors to facilitate the observation of their self-cleaning performance. The specific test results are as follows: Fig.13 The results show that the shapes of all the test samples did not change, and there was no water stain or color deposition of the dyeing solution on the surface of the film, proving that the photothermal super-hydrophobic coating prepared in this application has excellent cold and heat and acid-base stability, and the surface has good self-cleaning properties.
[0114] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A photothermal super-hydrophobic composite film, characterized in that: The photothermal super-hydrophobic composite membrane comprises a PVDF nanofiber base membrane, a photothermal layer attached to the PVDF nanofiber base membrane, and a hydrophobic layer attached to the photothermal layer.
2. The photothermal super-hydrophobic composite film according to claim 1, characterized in that: The photothermal layer includes light-absorbing nanoparticles, a stabilizer and an oxidant; the light-absorbing nanoparticles are polypyrrole nanoparticles, the stabilizer is polyvinyl alcohol, and the oxidant is one or more selected from FeCl3, FeCl3.6H2O; and / or, the hydrophobic layer includes functional particles, a hydrophobic modifier and a curing agent; the functional particles are one or two selected from titanium dioxide and silicon dioxide, the hydrophobic modifier is a polydimethylsiloxane prepolymer, and the curing agent is a polydimethylsiloxane curing agent.
3. The photothermal super-hydrophobic composite film according to claim 2, characterized in that: The mass ratio of light absorbing nanoparticles, stabilizer and oxidant in the photothermal layer is 0.1-2:0.1-0.5:1-10; and / or the mass ratio of functional particles, hydrophobic modifier and curing agent in the hydrophobic layer is 0.1-10:0.1-10:0.01-1.
4. The photothermal super-hydrophobic composite film according to claim 1, characterized in that: The photothermal super-hydrophobic composite membrane also includes a cross-linking agent for fixing the photothermal layer to the PVDF nanofiber base membrane; preferably, the cross-linking agent is glutaraldehyde.
5. The photothermal super-hydrophobic composite film according to claim 1, characterized in that: The thickness of the photothermal super-hydrophobic composite film is 60-100 μm; and / or the surface water contact angle of the photothermal super-hydrophobic composite film is greater than 150°.
6. A method for preparing a photothermal super-hydrophobic composite film according to any one of claims 1 to 5, characterized in that: The method comprises coating a dispersion of a photothermal layer on the surface of a PVDF nanofiber base film to form a photothermal layer and coating a dispersion of a hydrophobic layer on the surface of the photothermal layer to prepare a photothermal super-hydrophobic composite film.
7. The preparation method according to claim 6, characterized in that: The PVDF nanofiber base membrane is prepared by electrospinning. Preferably, the electrospinning solution uses DMF and / or acetone as solvent, and the concentration of PVDF in the spinning solution is 10-20wt%; and / or the electrospinning parameters are any one or more of the following: pushing speed is 1-10μL / min, voltage is 25-40kV, collection distance is 10-20cm, spinning temperature is 20℃-30℃, and spinning humidity is 20%-40%.
8. The preparation method according to claim 6, characterized in that: The photothermal layer dispersion is sprayed onto the surface of the PVDF nanofiber base film to form a photothermal layer. The coating amount of the photothermal layer dispersion is 0.1-10 ml / cm 2 ; and / or, the method further comprises immersing the PVDF nanofiber base membrane coated with the photothermal layer in a cross-linking solution to cross-link and fix the photothermal layer, wherein the cross-linking solution comprises a cross-linking agent and a solvent, wherein the cross-linking agent is glutaraldehyde, and the solvent is one or more of acetone, water, ethanol, and ether.
9. The preparation method according to claim 6, characterized in that: The dispersion liquid of the photothermal layer is formed by dispersing the material in the photothermal layer with a solvent, the solvent is selected from deionized water, and the amount of the solvent added is 5 to 20 mL based on the amount of 1 g of stabilizer added; and / or, the dispersion liquid of the hydrophobic layer is formed by dispersing the material in the hydrophobic layer with a solvent, the solvent is selected from one or more of ethyl acetate and n-hexane, and the amount of the solvent added is 100 to 500 mL based on the amount of 1 g of functional particles added.
10. The preparation method according to claim 8, characterized in that: The solvent in the cross-linking solution is acetone and water, and the volume ratio of acetone to water is 1-5:1; and / or, the pH of the cross-linking solution is 1-3; and / or, the concentration of the cross-linking agent in the cross-linking solution is 0.5wt%; and / or, the cross-linking time is 2h; and / or, the method further comprises spraying the dispersion of the hydrophobic layer onto the surface of the cross-linked photothermal layer, and the coating amount of the dispersion of the hydrophobic layer is 0.1-10ml / cm 2 .
11. The preparation method according to claim 6, characterized in that: The method further comprises a solvent welding step, wherein the solvent welding is to place the coated photothermal super-hydrophobic composite film at 60 to 100° C. for 3 to 10 hours.
12. Use of the photothermal super-hydrophobic composite film as claimed in claims 1 to 5 as an anti-icing film.
Citation Information
Patent Citations
Photo-thermal low-temperature anti-icing pasting pad
CN108893070A
Hydrophilic photo-thermal coating and preparation method thereof as well as hydrophilic photo-thermal material and preparation method thereof
CN114045073A
Photo-thermal super-hydrophobic anti-icing and deicing coating and preparation method thereof
CN116376414A
A superhydrophobic coating method
WO2023129058A2
Cited By
Gradient composite material with photo-thermal and super-hydrophobic properties as well as preparation method and application of gradient composite material
CN120228972A
A gradient composite material with photothermal and superhydrophobic properties and a preparation method and application thereof
CN120228972B